On osculation, superosculation and characteristic points - Grinbergs, Emanuels (My University, 1943)
Translated into English by D. Zeps Original text: Par oskulāciju, superoskulāciju un charakteristiskiem punktiem, https://dspace.lu.lv/dspace/handle/7/46435 Facsimile of the manuscript of dissertation: https://dspace.lu.lv/dspace/handle/7/46446 Facsimile of the manuscript of computations: https://dspace.lu.lv/dspace/handle/7/46433 Page numbers in translation are from original in Latvian
Keywords: differential geometry, osculating cylinder